Management of Outing Class Activities in Early Childhood Education: Learning Local Foods through Market Visits - Khairunnisa, Tiara; Azzahra, Agis Nur; Arti, Cantika Nisa Nur Indi; Panjaitan, Ivana Dewi; Dako, Nindi Andalas; Abdillah, Thalita Nur; Sjamsir, Hasbi; Rozie, Fachrul (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study aims to describe the management of outing class activities in early childhood education (PAUD) focused on learning about local foods through market visits. The background of this study is rooted in the importance of managing learning activities based on real-life experiences relevant to the lives of young children. The research employed a qualitative descriptive approach, utilizing direct observations and interviews at Al-Kautsar Kindergarten in Samarinda. The results indicate that the institution has implemented effective educational management principles through systematic planning, implementation, and evaluation of outing class activities. Children are invited to visit Segiri Market to learn about various local foods, understand basic buying and selling processes, and foster an appreciation for local culture. This activity aligns with the implementation of the Merdeka Curriculum, which emphasizes in-depth and contextual learning. The management of outing class activities at Al-Kautsar Kindergarten has proven effective in creating active, enjoyable, and meaningful learning experiences for young children.